2000
DOI: 10.1046/j.1365-201x.2000.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the creatine/phosphocreatine system in the regulation of mitochondrial respiration

Abstract: The mechanism of metabolic regulation of mitochondrial respiration in cardiac muscle cells was studied experimentally in the permeabilized heart fibres of mice and by computer modelling in silico. The experiments showed that the rate of mitochondrial respiration could be controlled by local production of ADP by mitochondrial creatine kinase in the intermembrane space of mitochondria. The spatially inhomogenous reaction-diffusion model of compartmentalized energy transfer was used to analyse which metabolite le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 22 publications
(13 reference statements)
7
66
0
1
Order By: Relevance
“…For example, the widely used model of Korzeniewski and Zoladz [4][5][6] invokes an empirical linear relationship between the difference in pH across the mitochondrial inner membrane (matrix pH minus cytosol pH) and the magnitude of inner membrane potential. While the Korzeniewski model has been validated and verified based on a number of studies and is widely applied [7][8][9], the central empirical relationship between electrostatic potential and pH difference is not expected to apply under all conditions. For example, in the extensive study of isolated cardiac mitochondria published by Bose et al [10], this relationship is not obeyed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the widely used model of Korzeniewski and Zoladz [4][5][6] invokes an empirical linear relationship between the difference in pH across the mitochondrial inner membrane (matrix pH minus cytosol pH) and the magnitude of inner membrane potential. While the Korzeniewski model has been validated and verified based on a number of studies and is widely applied [7][8][9], the central empirical relationship between electrostatic potential and pH difference is not expected to apply under all conditions. For example, in the extensive study of isolated cardiac mitochondria published by Bose et al [10], this relationship is not obeyed.…”
Section: Introductionmentioning
confidence: 99%
“…This latter study also showed reduced activation-stimulated oxyhaemoglobin delivery to the activated area following creatine supplementation. This suggests that creatine supplementation is acting to smooth fluctuations in the blood oxygen level dependent response curve which results from brain activation (Gjedde et al 1999;Madsen et al 1999), possibly by altering rates of ATP synthesis in the mitochondrion through the mitochondrial creatine kinase-adenine nucleotide translocase-porin complex (Wallimann et al 1992;Saks et al 2000). Most recently, deletion of cytosolic brain-type creatine kinase in mice was shown to result in slower learning of a spatial task and diminished open-field habituation as well as increased intra-and infra-pyramidal hippocampal mossy fibre area suggesting that the creatine-creatine kinase network is also involved in brain plasticity in addition to metabolism ( Jost et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of control of oxidative phosphorylation is through feedback of substrates for ATP synthesis. No additional regulatory mechanisms, such as feed-forward control of certain enzymes via cytosolic calcium levels (9) or functional coupling between mitochondrial creatine kinase and ANT (23,26,27), are necessary to explain the majority of the observed data. In addition, the impact of specific protein deficiencies on the relationship between oxidative phosphorylation and cytoplasmic ADP and P i is successfully explained by making the appropriate modifications to the mitochondrial enzymes altered in the diseases.…”
mentioning
confidence: 99%
“…Although the central component of the model-mitochondrial oxidative phosphorylation-is based on a mitochondrial model previously developed to match data on isolated mitochondria from rat heart, the integrated model matches a rich set of data on in vivo phosphate compounds from human skeletal muscle in healthy and complex I deficient individuals. The model also produces reasonable predictions for the ANT deficient subject, although the data available for comparison are sparse.The analysis predicts that the rate of oxidative phosphorylation is primarily regulated through concentrations of the substrates for ATP synthesis (ADP and P i ), since no additional control mechanisms, such as feed-forward control of certain enzymes via cytosolic calcium levels (9) and functional coupling between mitochondrial creatine kinase and ANT (23,26,27) that have been proposed to operate in the heart, were incorporated into the model. The current analysis does not rule out the possibility that ancillary control mechanisms are active in skeletal muscle (16,28); however, it shows that major contributions of such mechanisms to the overall regulation of the mitochondrial ATP synthetic pathway are not necessary to explain the thrust of the observed data.…”
mentioning
confidence: 99%